Concurrence of polyostotic fibrous dysplasia and spinal aspergillus in non-immunocompromised adult patient:case report - Pasahan, Ramazan; Akif Durak, Mehmet; Arif Aladag, Mehmet; Nur Akatli, Ayse; Okan Yildirim, Ismail (Annals of Medical Research, 2021)
None